Evaluation of the levels of interleukins IL-4, IL-13, IL-5, IL-10 and IL-33 in atopic dermatitis patients with and without dupilumab therapy - Jarmila Čelakovská; Eva Čermáková; Petra Boudková; Jan Krejsek (Frontiers in Immunology)
BackgroundInterleukins IL-4, Il-5, IL-10, IL-13 and IL-33 play an important role in atopic dermatitis patients. The aim of our study is to address several knowledge gaps in the understanding of interleukin dynamics in atopic dermatitis patients and the effects of dupilumab treatment.MethodWe conducted an assessment of plasma levels of interleukins IL-4, IL-5, IL-10, IL-13 and IL-33 in 89 AD patients and in 44 healthy individuals as a control group. The group of AD patients consisted of 27 patients treated with dupilumab (15 men, 12 women) at a mean age of 44.8 years and 62 patients without dupilumab treatment (35 women and 27 men) at a mean age of 46.3 years. The control group consisted of 44 healthy subjects (22 men, 22 women), at a mean age of 43.3 years. Patients were treated with a standard dose of dupilumab, 300 mg s.c. every two weeks. For screening analysis of plasma levels of selected cytokines, the performance assay Human cytokine Luminex was used. Blood samples were unstimulated and stimulated with phorbol myristate acetate and ionomycin. This stimulation provides non-specific stimulation of innate and adaptive immunity cells and increases their cytokine production. The level of interleukins IL-4, IL-5, IL-10, IL-13 and IL-33 were compared in AD patients with the results in control group. Nonparametric Kruskal-Wallis analysis of variance with post-hoc Dunn’s test with Bonferroni modification of significance level was used.ResultsThe significantly higher plasma level of stimulated IL-5 was confirmed in AD patients treated with dupilumab and significantly higher plasma IL-10 levels were confirmed in both dupilumab and non-dupilumab treated patients compared to control group. Stimulated IL-4 levels are significantly higher in patients treated with dupilumab compared to patients without dupilumab. The significant difference in IL-13 and IL-33 in AD patients compared to control group was not confirmed.ConclusionBy identifying significant differences in IL-5 and IL-10 plasma levels, our study highlights potential markers that could improve AD diagnosis and treatment monitoring. Our results contribute to a deeper understanding of how dupilumab alters immune signaling and may inform the development of additional biomarkers and targeted therapies for AD.